2017
DOI: 10.1038/modpathol.2016.180
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid sclerosing mucoepidermoid carcinoma with eosinophilia: a clinicopathologic and molecular analysis of a distinct entity

Abstract: Sclerosing mucoepidermoid carcinoma with eosinophilia is a rare thyroid neoplasm of uncertain pathogenesis that resembles salivary gland mucoepidermoid carcinoma. This multi-institutional study characterizes the clinicopathologic and molecular features of this tumor by utilizing next-generation sequencing to assess common mutations and gene fusions involved in thyroid carcinogenesis as well as fluorescence in-situ hybridization for MAML2 translocations typical of salivary gland mucoepidermoid carcinoma. Nine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 32 publications
4
57
1
Order By: Relevance
“…No recurrence or distant metastasis was detected during the follow-up period (20 years in case 1, 3 years in case 2, and 18 months in case 3). Shah et al concluded that the overall and recurrence-free survival of SMECE may be lower than those for other well-differentiated thyroid cancers [17], but we believe that outcomes are favorable when diagnosis is made at an early stage, such as in our cases. Ultrasound and FNAC of SMECE have not been well documented.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…No recurrence or distant metastasis was detected during the follow-up period (20 years in case 1, 3 years in case 2, and 18 months in case 3). Shah et al concluded that the overall and recurrence-free survival of SMECE may be lower than those for other well-differentiated thyroid cancers [17], but we believe that outcomes are favorable when diagnosis is made at an early stage, such as in our cases. Ultrasound and FNAC of SMECE have not been well documented.…”
Section: Discussionmentioning
confidence: 69%
“…Microscopically, thyroid SMECE is characterized by a combination of nested epidermoid carcinoma cells, intermediate carcinoma cells, and mucous-secreting carcinoma cells, fibrohyaline stroma, and prominent eosinophilic and lymphoplasmacytic infiltrates [10][11][12][13][14][15][16][17][18][19]. All of our cases showed these features.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations